2015
DOI: 10.1016/j.rmed.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Once-daily tiotropium Respimat® 5 μg is an efficacious 24-h bronchodilator in adults with symptomatic asthma

Abstract: Lung function improvements with tiotropium Respimat(®) add-on to medium-dose ICS were sustained and similar for once-daily 5 μg and twice-daily 2.5 μg, supporting tiotropium Respimat(®) 5 μg as a once-daily bronchodilator that provides efficacy over the whole 24-h dosing interval in patients with symptomatic asthma. ClinicalTrials.gov identifier: NCT01152450.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 14 publications
2
46
0
1
Order By: Relevance
“…In studies of patients with mild or moderate disease receiving maintenance treatment with ICS alone, tiotropium improved lung function and asthma control [5,7,8,10,11,13], and similar efficacy was confirmed in three studies comparing the efficacy of tiotropium with salmeterol as add-on to ICS [5,7,10]. In patients with more severe asthma e symptomatic despite treatment with ICS (!800 mg budesonide or equivalent) plus a LABA e a short-term trial demonstrated significant improvements in lung function following tiotropium add-on therapy [6].…”
Section: Introductionmentioning
confidence: 83%
“…In studies of patients with mild or moderate disease receiving maintenance treatment with ICS alone, tiotropium improved lung function and asthma control [5,7,8,10,11,13], and similar efficacy was confirmed in three studies comparing the efficacy of tiotropium with salmeterol as add-on to ICS [5,7,10]. In patients with more severe asthma e symptomatic despite treatment with ICS (!800 mg budesonide or equivalent) plus a LABA e a short-term trial demonstrated significant improvements in lung function following tiotropium add-on therapy [6].…”
Section: Introductionmentioning
confidence: 83%
“…1,8 Clinical studies in adults have demonstrated that tiotropium administered through the Respimat Soft Mist inhaler (Boehringer Ingelheim, Ingelheim am Rhein, Germany) is an effective and well-tolerated add-on treatment to at least ICS maintenance therapy in patients with mild, moderate, or severe symptomatic asthma. [9][10][11][12][13][14][15][16] The 2015 revision of the Global Initiative for Asthma strategy includes 5 mg of tiotropium administered through the Respimat device as an option for addition to ICS plus a LABA treatment at steps 4 and 5 in adults with a history of 1 Phase II studies in adolescents and children have shown similar lung function benefits to those observed in adults when tiotropium Respimat is added to at least ICSs. 17,18 We present results from a 1-year phase III study designed to examine the efficacy and safety of 2 doses (5 and 2.5 mg) of oncedaily tiotropium Respimat compared with placebo when added to background treatment with ICS maintenance therapy with or without a leukotriene receptor antagonist (LTRA) in adolescents with moderate symptomatic asthma.…”
mentioning
confidence: 99%
“…Both once-daily 5 µg and twice-daily 2.5 µg provided significant and comparable 24-h bronchodilation (compared with placebo: once-daily 5 µg, 158 mL; twice-daily 2.5 µg, 149 mL (both p<0.01)), with improvements in peak FEV1, trough FEV1, and morning and evening PEF that were also statistically significant with both dosing regimens (table 1). Tiotropium add-on therapy significantly improved mean ACQ-7 score (compared with placebo: once-daily 5 µg, −0.274 ( p<0.01); twice-daily 2.5 µg, −0.190 ( p<0.01)) and adverse events were comparable between all treatment regimens (table 2) [57].…”
Section: Tiotropium Add-on Therapy Delivered Via the Respimat Soft MImentioning
confidence: 93%